Third-order nonlinear optical properties of cyanine dyes with click chemistry modification. (February 2018) - Han, Pengbo; Wang, Dong; Gao, Hong; Zhang, Jingjing; Xing, Yan; Yang, Zhou; Cao, Hui; He, Wanli
Abstract: A series of organic NIR third-order NLO cyanine dyes were designed and synthesized using a Sonogashira coupling reaction and the high-yielding [2 + 2] click reaction. The photophysical and the click reactions were characterized by means of UV/Vis absorption spectroscopy. The electrochemical properties were characterized by means of cyclic voltammetry. In addition, the third-order nonlinear properties, including the nonlinear susceptibilities and the nonlinear absorption, were measured by using Z-scan techniques. The novel cyanine dyes show excellent water solubility, and many different properties comparing with our previous work. It was surprisingly found that the new click compounds also retained the properties of the original cyanine dye while extending the absorption wavelength to the near infrared region. The fascinating advantages mentioned above were exactly what we need. Furthermore, these dyes with click chemistry modification exhibited a typical reserve saturable absorption (RSA)-saturable absorption (RA) transition and strong nonlinear refraction. All of the click compounds showed the considerable third-order susceptibility χ (3) values. The results of these studies can provide new molecular-design strategies for third-order nonlinear optical materials for photoelectric and biological fields. Graphical abstract: Highlights: A sample and high-yielding synthesis way for cyanine dyes is proposed. A broad range of absorptivities could be acquired, and the maximum absorption wavelength reached the near infrared region. The ionized cyanine dye allows the dye molecules to be the effective NIR water-soluble nonlinear optical molecules.